Psychological features of hockey players with different stress resistance - A. A. Elkin (Спортивная медицина: наука и практика, 2020)
Objective: to study emotional and characterological features of hockey players with different stress resistance. Materials and methods: 120 hockey players of the Junior Hockey League (JHL) aged from 16 to 21 years were involved in the study. Interviewing, evaluation of medical records, test of differential self-assessment of the functional state (SAN) and method of personality research using the questionnaire FPI (modified form B) were conducted. Results: according to the results of the study, it was found that hockey players with high stress resistance had significantly lower rates on the scales of neuroticism, depression, irritability, emotional lability, as well as significantly higher rates on the scales of sociability, openness, well-being and mood (p<0.05). On the contrary, hockey players with low stress resistance had opposite features. Also, hockey players with high stress resistance had a higher sports experience, as well as better health. Conclusions: stress-resistance of players has significantly high connection with neurotism and irritability, as well as significant moderate negative association with age and sports experience. It is established that with increasing of neuroticism and irritability, as well as reducing of the age and sports experience stress resistance of hockey players decreases. Taking into account the results of the study, in order to maintain health, prolong professional longevity and maintain the proper level of performance of hockey players, it is important to use an integrated approach that provides a whole group of activities: rationalization of work and rest, improvement of working conditions, optimization of microclimate in the team.